Critical point calculation for binary mixtures of symmetric non-additive hard disks - Gózdz, W.T.; Ciach, A. (Condensed Matter Physics, 2016)
We have calculated the values of critical packing fractions for the mixtures of symmetric non-additive hard disks. An interesting feature of the model is the fact that the internal energy is zero and the phase transitions are entropically driven. A cluster algorithm for Monte Carlo simulations in a semigrand ensemble was used. The finite size scaling analysis was employed to compute the critical packing fractions for infinite systems with high accuracy for a range of non-additivity parameters wider than in the previous studies. Обчислено значення критичних фракцiй заповнення для сумiшей симетричних неадитивних твердих дискiв. Цiкавою рисою даної моделi є факт, що її внутрiшня енергiя є нульовою i фазовi переходи мають ентропiйну природу. Використано кластерний алгоритм для моделювання Монте Карло у напiв-великому
ансамблi. Застосовано аналiз скiнченно-вимiрного скейлiнгу для прецизiйного обчислення критичних
фракцiй заповнення нескiнчених систем для ширшої областi параметра неадитивностi порiвняно iз попереднiми дослiдженнями.